2008
DOI: 10.1111/j.1447-0756.2008.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of human papillomavirus in the development of epithelial ovarian neoplasms in Italian women

Abstract: The presence of HPV could be an expression of a latent infection. In both positive and negative HPV ovarian neoplasms, cervix showed only chronic cervicitis and no signal for HPV DNA on PCR analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…In reviewing the reference list in these articles, we identified one more article. Of the 35 identified studies, 22 were considered relevant after thorough examination. The remaining 13 studies were excluded for the following reasons: they were case reports ( n = 4) ; the data from these were included in another study ( n = 3) ; the paper reported HPV prevalence in serum and not HPV DNA in ovarian cancer tissue ( n = 1) ; endometrial and ovarian cancer were not differentiated ( n = 1) ; the information about how data were acquired was inadequate ( n = 1) ; the study included fewer than five ovarian cancer cases ( n = 1) ; the study only included borderline tumors ( n = 1) or the study was retracted after publication because of an error ( n = 1) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In reviewing the reference list in these articles, we identified one more article. Of the 35 identified studies, 22 were considered relevant after thorough examination. The remaining 13 studies were excluded for the following reasons: they were case reports ( n = 4) ; the data from these were included in another study ( n = 3) ; the paper reported HPV prevalence in serum and not HPV DNA in ovarian cancer tissue ( n = 1) ; endometrial and ovarian cancer were not differentiated ( n = 1) ; the information about how data were acquired was inadequate ( n = 1) ; the study included fewer than five ovarian cancer cases ( n = 1) ; the study only included borderline tumors ( n = 1) or the study was retracted after publication because of an error ( n = 1) .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included are presented in Table . In most studies, the subjects were women with ovarian cancer of epithelial origin , and ovarian cancer was classified into histological subtypes , serous ovarian cancer being the most common. Two publications failed to report the type of ovarian malignancy .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations